Impacts of Inflation Rate to the Price of School Supplies of Grade 12 Humanities and Social Sciences at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the most well-known economic problems is the contentious topic of inflation followingthe Covid-19 pandemic. Several people expressed their opinions when the cost of living in thePhilippines suddenly rose so sharply above that of other countries. The elderly, parents,employers, and students in Grade 12 who study Humanities and Social Sciences suffer fromthe consequences of inflation on a daily basis in the Philippines. This challenge may have avariety of detrimental impacts on students, such as increases in the cost of tuition, necessities,food, and even transportation. Several students decided to budget their money wisely in orderto continue attending their regular classes at school as a result of inflation.The results also showed the impact of the inflation rate on the price of school supplies in termsof basic needs that are always encountered by the students, with an overall mean is 3.16 asStrongly Agree, and in terms of school supplies with the weighted mean is 3.18 as StronglyAgree as the response of Grade 12 Humanities and Social Science students at BestlinkCollege of the Philippines, and the challenges that are sometimes encountered in terms ofFinancial with weighted mean is 2.85 as Agree. For the challenges that affect the inflation ratein terms of food prices, the weighted mean is 3.22.The result shows that the inflation rate to the price of school supplies in terms of transportationwith the weighted mean is 3.26, and in terms of tuition costs with the weighted mean, it is 3.26as strongly Agreeable. The result of the action can be forwarded as a recommendation. Someof the respondents Strongly Agree with the statement "Explore student discounts," which hasa weighted mean of 3.12 and got the 8th rank. Most of the respondents Strongly Agree withthe statement with a weighted mean of 3.30, "Reduce your utility bills," which has a weightedmean of 3.36 and got the rank 1st.
Keywords: Education